THE EFFECT OF SERVICE MARKETING MIX ON CUSTOMER SATISFACTION AT PT. BANK DANAMON INDONESIA, Tbk MAMUJU UNIT SUB-BRANCH - Suriadi, Suriadi; Fadlina, Fadlina; Rahman, Usman (Universitas Ichsan Sidenreng Rappang, 2023)
This study entitled The Effect of Service Marketing Mix on Customer Satisfaction at PT. Bank Danamon Indonesia, Tbk Mamuju Unit Sub-Branch which aims to determine the effect of products, promotions and processes on customer satisfaction. The method of analysis used in this research is 1) The validity test to measure the variables in this study has a correlation coefficient that is more than rtable = 0.165 (rtable value for n = 100), so that all questions are valid, 2) The reliability test shows that all Cronbach's Alpha variables which are quite large, namely above 0.60 so that it can be said that all measuring concepts for each variable from the questionnaire are reliable so that henceforth the concept variables are suitable for use as measuring instruments, and 3) The multiple regression results test above shows that the variable independent product, promotion, process influence the dependent variable namely customer satisfaction. Where every increase that occurs in the independent variable will also be followed by an increase in the dependent variable. In addition, from these results it can be seen that the dominant independent variable is the person/employee variable of 0.344.